2015
DOI: 10.1186/s13104-015-1777-5
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine induced pancytopenia leading to severe sepsis: an unusual early complication

Abstract: BackgroundClozapine is a second generation antipsychotic used to treat resistant schizophrenia and other psychotic illnesses. Leucopenia or agranulocytosis is a rare side effect of this drug. Pancytopenia is an extremely rare side effect of clozapine and literature review showed only one such case in where the pancytopenia developed several months after starting clozapine together with other antipsychotic drugs.Case presentationA 26-year-old Sri Lankan male was admitted with fever for 3 days. Apart from genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Usually, the recovery of blood dyscrasia occurs after 4 weeks of stopping clozapine. [ 4 ] This patient recovered completely from clozapine-induced bicytopenia within 3-week period. It is important to monitor blood counts in each patient receiving clozapine at baseline as well as subsequently on follow-up as per the guidelines to prevent any serious consequences.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Usually, the recovery of blood dyscrasia occurs after 4 weeks of stopping clozapine. [ 4 ] This patient recovered completely from clozapine-induced bicytopenia within 3-week period. It is important to monitor blood counts in each patient receiving clozapine at baseline as well as subsequently on follow-up as per the guidelines to prevent any serious consequences.…”
Section: Discussionmentioning
confidence: 91%
“…[ 2 ] Agranulocytosis makes patient susceptible to other infections because of impairment in the immunity. Literature shows only a few case reports of clozapine-induced pancytopenia [ 3 4 ] and still less literature is available for the occurrence of bicytopenia (reduced red blood cells [RBCs] and white blood cells [WBC]) due to clozapine. Pancytopenia is a medical condition in which there is a reduction in platelets and the number of WBCs and RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…Ponsford M reported that the use of clozapine substantially decreased immunoglobulin levels, potentially contributing to higher rates of pneumonia and mortality related to sepsis ( 41 ). A case report showed that a schizophrenia patient who received clozapine for 4 weeks was diagnosed with clozapine-induced pancytopenia complicated by severe sepsis ( 42 ). In the future, it may be more accurate to evaluate the causal association between schizophrenia and sepsis after eliminating the confounding factor of clozapine.…”
Section: Discussionmentioning
confidence: 99%
“…Among the blood dyscrasias associated with antipsychotic use, neutropenia is the most frequently observed, while thrombocytopenia occurs less frequently. Pancytopenia induced by psychotropic medications is an exceptionally rare adverse event, with predominant documentation concerning clozapine [2,3]. Nonetheless, isolated reports have also sporadically linked pancytopenia to atypical antipsychotics such as olanzapine, risperidone, and quetiapine [4][5][6], as well as, albeit more infrequently, with typical antipsychotics like perphenazine (a phenothiazine) [7].…”
Section: Introductionmentioning
confidence: 99%